Eksistensi Tari Dana-Dana sebagai Tari Pergaulan Remaja di Gorontalo: Fungsi, Adaptasi, dan Strategi Pelestarian - Rusni Podungge (Jurnal Bahasa, Sastra, dan Budaya, 2026)
Dana-Dana is a traditional Gorontalo dance that has served as a medium of social interaction among Muslim adolescents since the arrival of Islam in the region. Although it was designated as Indonesian Intangible Cultural Heritage in 2021, its function as a youth social dance has attracted little scholarly attention; earlier studies have concentrated on choreographic creativity and digital media adaptation. This study examines how that social function was historically formed, how it has shifted in contemporary performance practice, and which preservation strategies remain relevant. A qualitative descriptive design with document analysis was applied to official heritage records, academic publications, media reports, and audiovisual documentation of performances; the data were analysed through reduction, thematic classification, and source triangulation. The findings show that the social function of Dana-Dana emerged from a negotiation between the need for entertainment and Islamic norms governing interaction between unrelated men and women. In current practice the dance remains highly visible, yet its dominant function has moved from participatory social interaction toward aesthetic presentation for guests, tourism, and digital audiences. Preservation therefore requires more than documentation: it requires restoring participatory spaces in which adolescents dance for themselves rather than for spectators